HOURLY PRECIPITATION PATTERNS IN A BRAZILIAN TROPICAL CITY - Santos, Luiz octávio Fabrício dos; Machado, Nadja Gomes; Querino, Carlos Alexandre Santos; Pedreira Júnior, Altemar Lopes; Ivo, Israel Oliveira; Lotufo Neto, Névio; Biudes, Marcelo Sacardi (Revista Brasileira de Climatologia, 2021)
The research on precipitation is related to analysis of its spatiotemporal variability using daily, monthly and annual data. However, there is a scarcity in the availability of information on how this variable is distributed over the hours of the day. Thus, the objective of this study was to analyze the intensity and hourly patterns of precipitation in Cuiabá in the State of Mato Grosso. Precipitation data were collected at the Cuiabá weather station of the National Institute of Meteorology from 2003 to 2018. The relative frequency of hourly precipitation was analyzed by the Spiegel method. The relative frequency of precipitation in wet season was high in the afternoon from 16:00 h (6.2%) to 17:00 h (5.9%) and low in the morning from 10:00 (3.0%) to 11:00 (2.8%). The relative frequency of precipitation during the dry season was high at 05:00 h (5.0%) and 17:00 h (5.4%) and low from 12:00 h (2.6%) and 13:00 h (2.2%). In general, the intensity of precipitation in the region was predominantly weak, followed by moderate, strong and very strong. The precipitation events in Cuiabá generally occur in the late afternoon, resulting from convective activity in the region.